Characterizing the drivers of seedling leaf gas exchange responses to warming and altered precipitation: indirect and direct effects. (18th August 2015) - Smith, Nicholas G.; Pold, Grace; Goranson, Carol; Dukes, Jeffrey S.
Abstract : Climate change is expected to bring warmer temperatures and more variable precipitation patterns worldwide, patterns that will depend on the ability of the world's flora to take up carbon under these new conditions. We subjected deciduous tree seedlings growing in an old-field ecosystem in Massachusetts, USA to warming and altered precipitation. We found that leaf carbon uptake was greatest under the coolest, wettest conditions, an effect driven by increased soil water availability in these plots. Our findings suggest that warming may reduce leaf carbon uptake by decreasing soil moisture, an effect that will be exacerbated during drought periods. Abstract: Anthropogenic forces are projected to lead to warmer temperatures and altered precipitation patterns globally. The impact of these climatic changes on the uptake of carbon by the land surface will, in part, determine the rate and magnitude of these changes. However, there is a great deal of uncertainty in how terrestrial ecosystems will respond to climate in the future. Here, we used a fully factorial warming (four levels) by precipitation (three levels) manipulation experiment in an old-field ecosystem in the northeastern USA to examine the impact of climatic changes on leaf carbon exchange in five species of deciduous tree seedlings. We found that photosynthesis generally increased in response to increasing precipitation and decreased in response to warming. Respiration was less sensitive to the treatments. The net result was greater leaf carbon uptake in wetter and cooler conditions across all species. Structural equation modelling revealed the primary pathway through which climate impacted leaf carbon exchange. Net photosynthesis increased with increasing stomatal conductance and photosynthetic enzyme capacity ( V  cmax ), and decreased with increasing respiration of leaves. Soil moisture and leaf temperature at the time of measurement most heavily influenced these primary drivers of net photosynthesis. Leaf respiration increased with increasing soil moisture, leaf temperature, and photosynthetic supply of substrates. Counter to the soil moisture response, respiration decreased with increasing precipitation amount, indicating that the response to short- (i.e. soil moisture) versus long-term (i.e. precipitation amount) water stress differed, possibly as a result of changes in the relative amounts of growth and maintenance demand for respiration over time. These data (>500 paired measurements of light and dark leaf gas exchange), now publicly available, detail the pathways by which climate can impact leaf gas exchange and could be useful for testing assumptions in land surface models.